Hebridae, Gelastocoridae, and Mesoveliidae (Hemiptera: Heteroptera) from mangrove areas in Thailand - Khenmee, Areerat; Nakthong, La-au; Attawanno, Sajeemat; Sritipsak, Prabseuk; Dawwrueng, Pattarawich; Diloknorranart, Kulchon; Khongkhieo, Thitinat; Vitheepradit, Akekawat; Jantachid, Nattapont (Agriculture and Natural Resources, 2026)
Importance of the work: This is the first report of the family Gelastocoridae from a mangrove area in Thailand, providing a new country record for species and the family. Objectives: Providing a taxonomic list and distributions of Hebridae, Gelastocoridae, and Mesoveliidae in Thai mangroves. Materials and Methods: In total, 150 specimens were collected of the Hebridae, Gelastocoridae and Mesoveliidae from 24 localities during 2013–2024 in coastal mangrove areas of the Gulf of Thailand and the Andaman Sea using sweeping and hand-picking methods. Results: Specimens of Hebrus nereis (Polhemus and Polhemus, 1989) were collected from muddy margins of small streams and emergent rocks in mangrove forests in South Thailand. Three species of Mesoveliidae (Mesovelia vittigera Horvath, 1895, Mesovelia sp. and Nereivelia murphyi Polhemus and Polhemus, 1989) were collected. Female specimens of Mesovelia were reported from several mangroves in Central Thailand. One of these females was probably Mesovelia horvathi Lundblad, 1933; however, a male specimen is needed to confirm the identification. Specimens of the Mesoveliidae were collected from muddy margins with vegetation or dead logs. Nerthra macrothorax (Montrouzier, 1855) was a single species of Gelastocoridae collected among organic matter on a beach in mangroves in South Thailand. Main finding: A single species of the Hebridae was found restricted to South Thailand, whereas three species of the Mesoveliidae were collected throughout mangrove areas in Thailand. Furthermore, a species of the Gelastocoridae was reported from a single locality.